Educação Física, Qualidade de Vida e Saúde: campos de intersecção e reflexões sobre a intervenção - Fabiano Pries Devide (Universidade Federal do Rio Grande do Sul, 2002)
The objective of this paper is to think the relations between Physical Education, Quality of Life, and Health. Health is thought of as the central topic ofthe discussion, considering it as an intersection área between the other two. It is also considered as a key element of social representations of Physical Education, andprobably, of Quality of Life. The paper also points outsome aspects relatedto the complex and dynamic characteristics ofthe concept of Quality of Life; the relations between Physical Education and Health in the School; and its contributios to rethink about this new term Quality ofLife and the relations recently established with the área. The paper also suggests a re-orientation on the understandingofthese relations, overcoming the notion of causality between exercise-health-quality of life, through the idea of fragility ofthe responsibilities of Physical Education and its commitments with the questions relatedto the improvement ofQuality ofLife and Health.